Effect of abiotic stresses on the nondestructive estimation of rice leaf nitrogen concentration - Haefele, Stephan M.; Siopongco, Joel D. L. C.; Amarante, Serafin T.; Tuong, To Phuc (Hindawi Limited, 2010)
Decision support tools for non-destructive estimation of rice crop nitrogen (N) status (e.g., chlorophyll meter [SPAD] or leaf color chart [LCC]) are an established technology for improved N management in irrigated systems, but their value in rainfed environments with frequent abiotic stresses remains untested. Therefore, we studied the effect of drought, salinity, phosphorus (P) deficiency, and sulfur (S) deficiency on leaf N estimates derived from SPAD and LCC measurements in a greenhouse experiment. Linear relations between chlorophyll concentration and leaf N concentration based on dry weight (Ndw) between SPAD values adjusted for leaf thickness andNdwand between LCC scores adjusted for leaf thickness andNdwcould be confirmed for all treatments and varieties used. Leaf spectral reflectance measurements did not show a stress-dependent change in the reflectance pattern, indicating that no specific element of the photosynthetic complex was affected by the stresses and at the stress level applied. We concluded that SPAD and LCC are potentially useful tools for improved N management in moderately unfavorable rice environments. However, calibration for the most common rice varieties in the target region is recommended to increase the precision of the leaf N estimates.